2010
DOI: 10.1002/adfm.201000442
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled In‐Plane Growth of Mg2SiO4 Nanowires on Si Substrates Catalyzed by Au Nanoparticles

Abstract: In‐plane growth of Mg2SiO4 nanowires on Si substrates is achieved by using a vapor transport method with Au nanoparticles as catalyst. The self‐assembly of the as‐grown nanowires shows dependence on the substrate orientation, i.e., they are along one, two, and three particular directions on Si (110), (100), and (111) substrates, respectively. Detailed electron microscopy studies suggest that the Si substrates participate in the formation of Mg2SiO4, and the epitaxial growth of the nanowires is confined along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
(49 reference statements)
1
24
1
Order By: Relevance
“…It has been reported that Mg 2 SiO 4 grains can be produced by the coalescence of MgO and SiO 2 grains [16]. In addition, Mg 2 SiO 4 and MgSiO 3 also would be formed using Mg and Si substrate under the appropriate partial pressure of oxygen [15]. However, in this experiment, their absence in the final products indicated by the XRD and TEM results.…”
Section: Fig 4: Tem Images and Corresponding Fft Patterns Of The Nancontrasting
confidence: 47%
See 2 more Smart Citations
“…It has been reported that Mg 2 SiO 4 grains can be produced by the coalescence of MgO and SiO 2 grains [16]. In addition, Mg 2 SiO 4 and MgSiO 3 also would be formed using Mg and Si substrate under the appropriate partial pressure of oxygen [15]. However, in this experiment, their absence in the final products indicated by the XRD and TEM results.…”
Section: Fig 4: Tem Images and Corresponding Fft Patterns Of The Nancontrasting
confidence: 47%
“…• C) [15,18]. In other words, the reaction conditions of this experiment could not meet the requirement of the Mg 2 SiO 4 and Mg 2 SiO 3 formation.…”
Section: Fig 4: Tem Images and Corresponding Fft Patterns Of The Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is considered that the formation of Mg 2 Si should be preferred, which agrees with the results of this experiment. Additionally, the formation of Mg 2 SiO 4 and Mg 2 SiO 3 should be carried out at high temperatures (>800 o C) [14,16]. Thus, higher vacuum condition is expected to reduce the amount of O.…”
Section: Resultsmentioning
confidence: 99%
“…[2,6] Surface-directed vaporliquid-solid (SVLS) growth of nanocrystals [7] has become known for its desirable characteristics, namely, precise and predictable positioning/orientation and elimination of post-growth nanowire (NW) alignment. [8][9][10] This approach exploits the surface crystal information of the substrate to laterally guide nanocrystals in predictable directions and has been demonstrated on a variety of materials including ZnO, [7] GaAs, [10] In 2 O 3 , [11,12] GaN, [13] Ge, [11] Mg 2 SiO 4 , [14] TiO 2 , [8] and ZnSe. [15] The compatibility of the SVLS growth process with semiconductors and conventional optical photolithography is expected to lead to breakthroughs in transitioning nanosystems to complex 2D and 3D architectures and ultimately to practical applications.…”
Section: Introductionmentioning
confidence: 99%